Shattered Voices : Language, Violence, and the Work of Truth Commissions. (University of Pennsylvania Press, 2006)
Following periods of mass atrocity and oppression, states are faced with a question of critical importance in the transition to democracy: how to offer redress to victims of the old regime without perpetuating cycles of revenge. Traditionally, balance has been restored through arrests, trials, and punishment, but in the last three decades, more than twenty countries have opted to have a truth commission investigate the crimes of the prior regime and publish a report about the investigation, often incorporating accounts from victims. Although many praise the work of truth commissions for empowering and healing through words rather than violence, some condemn the practice as a poor substitute for traditional justice, achieved through trials and punishment. There has been until now little analysis of the unarticulated claim that underlies the truth commissions' very existence: that language -- in this case narrative stories -- can substitute for violence. Acknowledging revenge as a real and deep human need, Shattered Voices explores the benefits and problems inherent when a fragile country seeks to heal its victims without risking its own future. In developing a theory about the role of language in retribution, Teresa Godwin Phelps takes an interdisciplinary approach, delving into sources from Greek tragedy to Hamlet, from Kant to contemporary theories about retribution, from the Babylonian law codes to the South African Truth and Reconciliation Report. She argues that, given the historical and psychological evidence about revenge, starting afresh by drawing a bright line between past crimes and a new government is both unrealistic and unwise. When grievous harm happens, a rebalancing is bound to occur, whether it is orderly and lawful or disorderly and unlawful. Shattered Voices contends that language is requisite to any adequate balancing, and that a solution is viable only if it provides an atmosphere in which storytelling and subsequent dialogue can flourish. In the developing culture of ubiquitous truth reports, Phelps argues that we must become attentive to the form these reports take -- the narrative structure, the use of victims' stories, and the way a political message is conveyed to the citizens of the emerging democracy. By looking concretely at the work and responsibilities of truth commissions, Shattered Voices offers an important and thoughtful analysis of the efficacy of the ways human rights abuses are addressed. Teresa Godwin Phelps is Professor of Law and Director of the Legal Writing Program at the University of Notre Dame.